ドライバレー クッサク チョウサ 1975 76ネン タイ ホウコク - 中井, 信之; ナカイ, ノブユキ; 神沼, 克伊; カミヌマ, カツタダ; NAKAI, Nobuyuki; KAMINUMA, Katsutada (国立極地研究所, 1976)
P(論文) 日本,アメリカ,ニュージーランド三国共同観測事業のドライバレー掘削計画(DVDP)は,その計画が1年延長され,1975-76年のシーズンも実施された.掘削地点はドライバレーの東端,ニューハーバーから20kmのロス棚氷上で,DVDP No.15孔である.掘削準備は9月下旬から始まり,10月下旬にはすべての準備が終了した.11月5日から掘削を開始,21日,海底下64.6mまで掘ったところで,氷状が悪化してきたため,掘削を中止した.日本からの参加者は2名で,掘削,調査に参加し,掘削終了後はマクマード基地を基点に,マクマード海峡周辺の地学調査,地学研究室でのガス分析や地震観測などを実施した.11月4日,内陸のDome Cで輸送機が損傷し,ニュージーランド-マクマード間の輸送事情が悪化したため,マクマード基地に滞在する科学者が例年に比して非常に少なかった.このため,ヘリコプターを利用した野外調査が十分に実施できた. The Japanese party consisting of two members participated in the last field survey season, phase V of 1975-1976 Dry Valley Drilling Project (DVDP), in the McMurdo Sound region for the period from 27 October 1975 to 8 January 1976. The main international program of this field survey season was the drilling of submarine sediments in McMurdo Sound. As Japanese party's own project in relation to DVDP, microseismological observations at McMurdo Station and geochemical field survey in the coastal area of McMurdo Sound were also planned to investigate continental subsurface structures of Antarctica and to disclose the geological history of Dry Valleys and the McMurdo region. DVDP No. 15 drilling was performed from 5 to 21 November 1975 to obtain unconsolidated marine sediments. The drilling site was set on the sea ice of McMurdo Sound, 110km northwest of McMurdo Station and 20km east of New Harbor, Taylor Valley, and over 122m-thick sea water layer. Cored sediments were sampled down to 64.6m depth below the ocean floor surface and the recovery was rather good, being about 52%. Most of sediments are olive gray to olive black, fine- to coarse-grained basaltic sands, and can be divided into two units, with a depth of 12.5m as the boundary between the two. In the sediments from 63.6 to 64.6m, an unusually high concentration of CH_4 amounting to 37.9%, was detected by the portable gaschromatograph GC-30 AT at the drilling site but no heavier hydrocarbons were found. Three seismographs designed for recording micro-earthquakes were set at the foot of Observation Hill near McMurdo Station, Ross Island. ...